Timbuktu civilization and its significance in Islamic history - Shuriye, Abdi Omar; Sh. Ibrahim, Dauda (Publishing, Rome-Italy, 2013)
Timbuktu civilization began as a seasonal settlement for trade caravans in the early 11th century. It later flourished in trade and as one of the early African centres of Islamic culture. This paper reviews the trend of Timbuktu civilization from prehistoric period up to the current state of its political impact of the region. The paper further focuses on the role Timbuktu played in African history by serving as academic and commercial centre. The significant of this paper is to reveal the fact that Africa has a long Islamic civilization. The paper provides evidences from reliable sources of the symbolic representation of the impact and influence of the early schools and universities between 11th and 15th century that existed in West Africa. The manuscript of Timbuktu serves as a living testimony of the highly advanced and refined civilization in Africa during the middle ages. The history of monuments, artefacts as well as architectural land marks that signifies the historical origin of this ancient city is presented. The early heroes that stood firm towards the development and civilisation of Timbuktu are outlined. Analysis of the development as well as the factors that led to the civilization is presented in this paper.